Use of Artificial Neural Networks to Identify Fake Profiles - Jabeen, Falak; Biradar, Veeresh; Nase, Gururaj (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2022)
There is a tremendous increase in technologies these days. Mobiles are becoming smart. Technology is associated with online social networks which has become a part in every one’s life in making new friends and keeping friends, their interests are known easier. But this increase in networking online makes many problems like faking their profiles, online impersonation having become more and more in present days. Users are fed with more unnecessary knowledge during surfing which are posted by fake users. Researches have observed that 20% to 40% profiles in online social networks like Facebook are fake profiles. Thus, this detection of fake profiles in online social networks results into solution using frameworks. How to cite this article: Jabeen F, Biradar V, Nase G. Use of Artificial Neural Networks to Identify Fake Profiles. J Adv Res Appl Arti Intel Neural Netw 2021; 5(2): 23-27.